Visual Storytelling Learning Method for Early Childhood - Alfakihuddin, Lukman Baihaqi; Tjhin, Santo; Setiawan, Iwan (Center for Research and Community Service of Sampoerna University, 2024)
The community service carried out by the SERASA team from Sampoerna University at PAUD Jala Benaya, Penjaringan, North Jakarta, on June 8, 2023, aims to improve teacher competence and introduce the use of visual media and artificial intelligence-based technology in early childhood learning. With the theme “Visual Storytelling Learning Methods for Early Childhood”, this activity consisted of training and workshops attended by PAUD teachers and students of PAUD Jala Benaya. In this workshop, teachers were given knowledge about their role in creating a conducive learning environment, the importance of structured learning planning, as well as an understanding of visual learning styles and educational technology. Preschool students were also given the opportunity to learn using AI technology through several interactive websites. This activity showed that ECD teachers gained a deeper understanding of the use of visual media and technology in learning, as well as more confidence in implementing technology in the classroom. Preschool students responded positively to the interactive learning methods provided, which increased their interest in learning.